Henricus Sienkiewicz, Anthea, sive fabula 'Eamus ad Ipsum' a Petro Angelinio Latine versa, quam denuo edidit atque illustravit Theodericus Sacré. Bruxelles: Melissa, 2010. Pp. 177. ISBN 9782872900268. €20.00 - Jovanović, Neven, filolog (Array, 2011)
Foundation Melissa, Belgian "sodalitas perenni Latinitati dicata", recently started a book series Pluteus Neolatinus, dedicated to Latin texts written in the period 1750-1950. Its first title, edited and introduced by Dirk Sacré, is a homage both to Henryk Sienkiewicz (1846–1916), one of the most popular Polish writers at the turn of the 19th and 20th centuries, and to the translator Pietro Angelini (1847-1911), a Vatican prelate and teacher praised for his elegant Latin. At the same time, the book offers testimony to the late nineteenth-century fascination with the Graeco-Roman world of the Roman empire, as well as, for readers fluent in the language, a pleasurable opportunity to appreciate different styles of writing in neo-Latin (the book is in Latin from cover to cover, editor's preface and notes included).